Economic Relations Between Turkey And Africa: Challenges And Prospects - Tepecikliogu, Elem Eyrice (Journal of Sustainable Development Law and Policy, 2025)
African affairs occupied a secondary status in Turkish foreign policy until very recently. However, following the adoption of the Action Plan for Opening up to Africa in the late 1990s, Turkish politicians started to assign a higher priority to relations with African countries. The incumbent Turkish government now attaches great importance to developing long-term relations with those countries. We can also see that Africa’s image in Turkey is changing with journalists presenting new narratives about the continent and supporting Turkish involvement in African affairs. There is also an increasing interest in African studies in the academia, although scholarly work produced on African issues remains limited. This study explores the evolution of Turkish-African relations and concentrates mostly on Turkey’s economic engagement in African countries. It also seeks to analyse recent Turkish initiatives in Africa’s energy sector. The article argues, among other things, that although the low level of attention paid to African issues has changed, the pace of the development of relations with Africa is still slow and more steps have to be taken to further improve relations with African countries.